Deteksi Area Wajah Manusia Pada Citra Berwarna Berbasis Segmentasi Warna YCbCr dan Operasi Morfologi Citra - Moh La Andi Rais Imran Yatim; Jayanti Yusmah Sari; Ika Purwanti Ningrum (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
Face detection is one of the most important preprocessing steps in facial recognition systems used in biometric identification. Face detection is used to determine the location, size and number of faces in an image or video in various positions and backgrounds. One method used in face detection systems is segmentation based on skin color. In this study YCbCr skin color segmentation method and morphological operations were used. Based on the results of experiments conducted on 38 images, the system obtained an accuracy of 63.15%